2007
DOI: 10.1111/j.1439-0426.2007.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding different protein to energy (P/E) ratios on the growth performance and body composition of Oreochromis niloticus fingerlings

Abstract: SummaryThis study evaluated the growth performance and body composition of Oreochromis niloticus fingerlings (average initial weight 16.53 ± 0.44 g) fed 9 experimental diets (A, B, C, D, E, F, G, H and I) containing three different levels of protein (26, 31 and 36 g 100 g )1 ) at three different gross energy (GE) levels (16, 19 and 22 MJ kg) for a period of 64 days. Significant differences were observed in the feed consumption, body weight gain, specific growth rate (SGR), condition factor (k), feed conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 37 publications
2
44
2
2
Order By: Relevance
“…Some studies have reported the relevance of the balance between protein and energy in fish diets (Bomfim et al, 2005;Cotan et al, 2006;Piedras et al, 2006;Ali et al, 2008). If this ratio is unbalanced during fish growth, the proteins in the diet can be used as energy source (Kubitza, 2000) or directed to protein metabolism (Meurer et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported the relevance of the balance between protein and energy in fish diets (Bomfim et al, 2005;Cotan et al, 2006;Piedras et al, 2006;Ali et al, 2008). If this ratio is unbalanced during fish growth, the proteins in the diet can be used as energy source (Kubitza, 2000) or directed to protein metabolism (Meurer et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The present findings also indicated a considerable reduction in PER with carp feed. An increase in the dietary energy level at lower dietary protein levels improves the efficiency of protein utilization and retention (Ali et al 2008). Therefore, this reduction in carp feed probably results from the low lipid content or the types of vegetable proteins, as is mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Proses ekskresi dan katabolisme asam amino tersebut membutuhkan energi yang banyak sehingga alokasi energi protein untuk meretensi protein dalam tubuhnya akan berkurang. Retensi protein dipengaruhi oleh berbagai faktor termasuk kandungan protein pakan, keseimbangan asam amino dan rasio energi pakan (Ali et al, 2008). Respons penurunan laju pertumbuhan ikan akibat protein tinggi dilaporkan terjadi pada ikan sidat A. japonica dan A. marmorata yang mengalami kenaikan laju pertumbuhan pada kadar protein 45% dan menurun pada kadar 50% (Okorie et al, 2007;Cheng et al, 2013).…”
Section: Pembahasanunclassified